Matlab graphical user interface (GUI) for digital image improvement - Lee, H. (University Malaysia Sarawak, UNIMAS., 2003)
The idea of this thesis is to improve the appearance quality of the degraded digital image. For the improvement purpose, three methods are used such as contract manipulation, image filtering and geometric transformation. This thesis might be the initial step for more detail research on the digital image processing where nowadays it becomes the major part of any new application development.